Using cocoa (Theobroma cacao) shell-based activated carbon to remove 4-nitrophenol from aqueous solution: Kinetics and equilibrium studies - Ahmad, Fisal; Daud, Wan Mohd Ashri Wan; Ahmad, Mohd Azmier; Radzi, Rosinah (Elsevier, 2011)
The cocoa shell (CS) flake was ground, sieved and pressed into pellets. The pellets were carbonized at 800 degrees C and subjected to activation at 850 degrees C under a flow of CO(2) for several activation burn off. The cocoa shell-based activated carbon (CSAC) showed moderate surface area (248 m(2) g(-1)), a low rnesoporosity ratio with a pore size in the range between 2 and 4 nm. CSAC also displays the presence of aliphatic, aromatic hydrocarbons, C=O and a near absence of C-O. CSAC was evaluated for its ability to adsorb 4-nitrophenol (4-NP). The adsorption time and initial dye concentration study on adsorption performance was carried out in a batch system. The results indicate that the Freundlich, Temkin and Langmuir isotherms fit well (R(2) > 0.9). The results from the kinetic study show that 4-NP adsorption follows pseudo-second-order and Boyd models. (C) 2011 Elsevier B.V. All rights reserved.